Parents' Strategies and Challenges in Educating Children in The Digital Era - Alda Mayrizka Augustine; Naila Fikrina Afrihlia (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
This study aims to examine the strategies and challenges faced by parents in raising children in the digital era. The background of this research is based on the rapid development of digital technology, which has brought significant changes in child-rearing patterns, while simultaneously giving rise to various risks and obstacles that need to be addressed. This study used a qualitative descriptive approach using observation, interviews, and documentation techniques. The research findings indicate that effective digital parenting strategies involve managing gadget use time, selecting educational content, open communication, and improving parental digital literacy. However, parents also face various challenges such as limited digital literacy, socio-cultural pressures, and the risk of exposure to negative content. This study underscores the importance of policy support and ongoing educational programs for parents to optimize their digital parenting role. It is hoped that the results of this study can serve as a foundation for developing more effective and contextual digital parenting policies and practices in Indonesia.